Renewable Energy Desalination : An Emerging Solution to Close the Water Gap in the Middle East and North Africa - World Bank (Washington, DC: World Bank, 2012)
The Middle East and North Africa (MENA) region is one of the most water-stressed parts of the world. In just over 25 years, between 1975 and 2001. Looking to the future, MENA's freshwater outlook is expected to worsen because of continued population growth and projected climate change impacts. The region's population is on the way to doubling to 700 million by 2050. Projections of climate change and variability impacts on the region's water availability are highly uncertain, but they are expected to be largely negative. To offer just one more example, rainfall and freshwater availability could decrease by up to 40 percent for some MENA countries by the end of this century. The urgent challenge is how to adapt to the future as illustrated by these numbers and how to turn the region's economy onto a sustainable path. This volume suggests new ways of thinking about the complex changes and planning needed to achieve this. New thinking will mean making better use of desert land, sun, and salt water the abundant riches of the region which can be harnessed to underpin sustainable growth. More mundane, but just as important, new thinking will also mean planning for dramatically better management of the water already available. Right now, water is very poorly managed in MENA. Inefficiencies are notorious in agriculture, where irrigation consumes up to 81 percent of extracted water. Similarly, municipal and industrial water supply systems have abnormally high losses, and most utilities are financially unsustainable. In addition, many MENA countries overexploit their fossil aquifers to meet growing water demand. None of this is sustainable while water resources decline. This volume hopes to add to the ongoing thinking and planning by presenting methodologies to address the water demand gap. It assesses the viability of desalination powered by renewable energy from economic, social, technical, and environmental viewpoints, and it reviews initiatives attempting to make renewable energy desalination a competitively viable option. The authors also highlight the change required in terms of policy, financing, and regional cooperation to make this alternative method of desalination a success. And as with any leading edge technology, the conversation here is of course about scale, cost, environmental impact, and where countries share water bodies plain good neighborly behavior.